Biodiversity of archaea in Manzala lake in Egypt based on 16S rRNA gene - Elsaied, H. E. (2007)
A first molecular genetic study was done on the diversity of archaeal communities in two sites, Bashtir and Genka, of the Manzala Lake, Egypt, based on culture-independent 16S rRNA gene analysis. Bulk microbial DNAs were extracted from surface water and sediment samples collected from both the two studied sites. The archaeal 16S rRNA gene was positively amplified from the DNAs of all samples by PCR. The amplicons were cloned and analyzed directly by sequencing followed by statistical and phylogenetic analyses. The results recorded 6, 10, 16 and 9 archaeal phylotypes in Bashtir water, Genka water, Bashtir sediment and Genka sediment, respectively. Based on Libshuff pairwise clone library comparisons, the 16S rRNA gene phylotypes from Bashtir sediment encompassed the phylotypes of Genka sediment, while the phylotypes of Genka sediment accounted only a minor portion of those of Bashtir sediment. The recovered phylotypes from water samples showed phylogenetic differentiation from those from sediment samples, an observation implicating the phylogenetic distinction between water and sediment archaeal communities. Several recovered phylotypes from water and sediment samples located in the phylogenetic branch of the phylum Euryarchaeota. On the other hand, the phylum Crenarchaeota characterized, mainly, the phylotypes recovered from sediment samples. In the term of affiliation to species, several phylotypes, mainly from water samples, closely related to known Euryarchaeotic methanogenic species Methanothrix soehngenii, Methanospirillum hungatei and Methanocorpusculum labreanum, implying uncommon occurrence of methanogens in surface waters. The Crenarchaeota- like phylotypes affiliated to the thermophilic species Thermofilum pendens and Staphylothermus achaiicus, implicating the global distribution of those species in even moderately temperate habitats like that of Manzala. Most of the recovered phylotypes belonged to unculturable archaeal species.
Includes references.
1
Keywords: Archaebacteria; Archaebacteria -- Genetics; Archaebacteria -- Cytogenetics; Polymerase chain reaction